221 Analysis 2, 2008–09 Suggested solutions to exercise sheet 4 Let (X, M, m) be a measure space. 1. Fix a measurable set B ∈ M. Show that the function mB : M → [0, ∞] given by mB (A) = m(A ∩ B) for A ∈ M, is a measure. Solution. We have mB (∅) = m(∅ ∩B) S = m(∅) = 0. If (Ai )i≥1 is a sequence of pairwise disjoint sets in M and AS = ∞ i=1 Ai , then (A Si∞∩B)i≥1 is a sequence ∞ of pairwise disjoint sets in M and i=1 (Ai ∩ B) = ( i=1 Ai ) ∩ B = A ∩ B. So ∞ X mB (Ai ) = i=1 ∞ X m(Ai ∩ B) = m i=1 S∞ i=1 (Ai ∩ B) = m(A ∩ B) = mB (A). So mB is countably additive. So mB is a measure. 2. (a) Let f : X → [0, ∞] be a nonnegative function and suppose that An ⊆ X with An ↑ X. Show that if fn = f χAn then fn ↑ f . (b) Show that if f : R → R is integrable (with respect to Lebesgue measure) then Z Z n f (x) dx = lim f (x) dx. n→∞ −n [First consider what happens if f (x) ≥ 0 for all x ∈ R and use the Monotone Convergence Theorem]. (c) Give an example Z nof a function f : R → R which is not integrable, but for which lim f (x) dx = 0. n→∞ −n S∞ Solution. (a) S∞We have A1 ⊆ A2 ⊆ A3 ⊆ . . . and n=1 An = X. Let x ∈ X. We have x ∈ n=1 An , so x ∈ An for some n ≥ 1. Let n0 ≥ 1 be the smallest such n. The sequence (fn (x))n≥1 = (0, 0, 0, . . . , 0, f (x), f (x), f (x), . . . ) is {z } | n0 −1 then increasing (since f (x) ≥ 0) with limit f (x). So for any x ∈ X, fn (x) ↑ f (x). So fn ↑ f . (b) Let An = [−n, n]. Suppose first that f : R → [0, ∞) and let fn = f χAn . Since An ↑ R we have fn ↑ f by (a), so by the Monotone Convergence Theorem, Z n Z Z Z f (x) dx = fn (x) dx → f (x) dx = f (x) dx as n → ∞. −n 1 if f : R → RR is any integrable function, previous paragraph, RNow R n − then byR the n ∞ ∞ + + f (x) dx → −∞ f (x) dx and −n f (x) dx → −∞ f − (x) dx as n → ∞. −n So Z n Z n Z n + f (x) dx = f (x) dx − f − (x) dx −n Z−n Z −n Z + − → f (x) dx − f (x) dx = f (x) dx as n → ∞. R (c) Let f (x) = x. Then |f (x)| dx = ∞, so f is not integrable. However, Rn Rn f (x) dx = x dx = 0 for any n. −n −n For the next two questions, work with the measure space (R, M, m) where M denotes the Lebesgue measurable subsets of R and m is Lebesgue measure. 3. (a) Let f : R → [0, ∞), f (x) = x χ[0,1) (x). Sketch the graph of f . (b) Find a monotone increasing sequence (ϕn )n≥1 of simple nonnegative measurable functions ϕn : R → [0, ∞) with ϕn ↑ f . [Hint: look at the proof of Theorem 26]. R (c) RFind ϕn dm and use the Monotone Convergence Theorem to find f dm. [Don’t use the Fundamental Theorem of Calculus!] (d) RLet I = R \ Q. Show that f = f χI almost everywhere, and compute f dm. I Solution. (a) [omitted] (b) The procedure in Theorem 26 is to approximate f (x) by rounding down to the nearest integer multiple of 2−n . Since f (x) = x for x ∈ [0, 1), we have ( k/2n if x ∈ [0, 1) and k ∈ Z with k/2n ≤ x < (k + 1)/2n ϕn (x) = 0 if x 6∈ [0, 1) So ϕn (x) = n −1 2X k=0 k χ[k/2n ,(k+1)/2n ) . 2n (c) We have Z n −1 Z 2X k χ[k/2n ,(k+1)/2n ) dm ϕn dm = 2n k=0 = = n −1 2X k=0 n −1 2X k=0 k m[ kn , k+1 n ) 2n 2 2 k 1 · 2n 2n n 2 −1 1 X 1 = 2n k = 2n · 21 (2n − 1) · 2n 2 k=0 2 = 1 2n − 1 = (1 − 2−n ). n 2·2 2 2 Since ϕn ↑ f , by the Monotone Convergence Theorem we have Z Z 1 1 f dm = lim ϕn dm = lim (1 − 2−n ) = . n→∞ n→∞ 2 2 (d) If x ∈ I then f (x) = f χI (x). So {x ∈ X : f (x) 6= f χI (x)} ⊆ R \ I = Q. Since Q is countable it has Lebesgue measure zero; so {x ∈ X R: f (x) 6= fR χI (x)} alsoRhas measure zero. So f = f χI almost everywhere. So f dm = f χI dm = I f dm. 4. (a) Let c ∈ R and let A be a Lebesgue measurable subset of R. Show that R R χA (x − c) = χA+c (x) and χA+c (x) dx = χA (x) dx. (b) Show that if ϕ : R → [0, ∞) is a simple nonnegative measurable function R R and ϕc : R → [0, ∞), ϕc (x) = ϕ(x − c) then ϕc dm = ϕ dm. (c) Use the Monotone Convergence Theorem to show that if f : R → [0, ∞] is a nonnegative measurable function and fc : R → [0, ∞] is given by R R fc (x) = f (x − c) then fc dm = f dm. (d) Show that if f : R → R is an integrable functionR and fc : RR → R is given by fc (x) = f (x − c) then fc is integrable, and fc dm = f dm. [You may use the fact that fc is measurable without proof.] Solution. (a) Recall that Lebesgue measure is translation invariant, so R R m(A + c) = m(A). But χA+c dm = m(A + c) and χA dm = m(A). Also, χA+c (x) = 1 ⇐⇒ x ∈ A + c ⇐⇒ x − c ∈ A ⇐⇒ χA (x − c) = 1, and otherwise χA+c (x) = 0 = χA (x − c). So χA+c = χA . P P P (b) Let ϕ(x) = ni=1 ai χAi . Then ϕc (x) = ni=1 ai χAi (x−c) = ni=1 ai χAi +c (x). So Z Z Z Z n n X (a) X ϕc dm = ai χAi +c dm = ai χAi dm = ϕ dm. i=1 i=1 (c) Let ϕn be a monotone increasing sequence of simple nonnegative measurable functions with ϕn ↑ f (such a sequence exists by Theorem 26). Then ϕn,c (x) = ϕn (x − c) defines a monotone increasing Rsequence of Rsimple nonnegative measurable functions with ϕn,c ↑ fc and ϕn,c dm = ϕn dm for each n ≥ 1 by (b). So by the Monotone Convergence Theorem, Z Z Z Z (b) M CT M CT fc dm = lim ϕn,c dm = lim ϕn dm = f dm. n→∞ n→∞ R R (d) If f is integrable then |f | dm < ∞, so by (c), we have |fc | dm < ∞. So fc is integrable, and since (fc )+ and (fc )− are nonnegative measurable functions, we can apply (c) to deduce: Z Z Z Z Z Z (c) + − + − fc dm = (fc ) dm − (fc ) dm = f dm − f dm = f dm. 3 5. Let f, g : X → [−∞, ∞] be two measurable functions. (a) If q ∈ Q, show that g −1 [−∞, q) and f −1 (q, ∞] ∩ g −1 [−∞, q) are both measurable sets. (b) Show that for any x ∈ X with f (x) > g(x), there is a rational number q with g(x) < q < f (x). Deduce that [ {x ∈ X : f (x) > g(x)} = f −1 (q, ∞] ∩ g −1 [−∞, q). q∈Q Why does this show that this set is measurable? (c) Deduce that the set {x ∈ X : f (x) 6= g(x)} is measurable. Solution. (a) We have [−∞, q) = {−∞} ∪ A where A is the Borel set A = (−∞, q). Since g is measurable, g −1 [−∞, q) is measurable. Since f is measurable, f −1 (q, ∞] is measurable. The measurable sets form a σ-algebra, so are closed under [countable] intersections. So f −1 (q, ∞] ∩ g −1 [−∞, q) is measurable. (b) If f (x) > g(x) then the open interval (g(x), f (x)) ⊆ R is not empty. So it contains a rational number q; so g(x) < q < f (x). S Let S = q∈Q f −1 (q, ∞] ∩ g −1 [−∞, q). If x ∈ X with f (x) > g(x) then f (x) > q and g(x) < q for some q ∈ Q, so x ∈ f −1 (q, ∞] ∩ g −1[−∞, q); so x ∈ S. Conversely, if x ∈ X with x ∈ S then x ∈ f −1 (q, ∞] ∩ g −1 [−∞, q) for some q ∈ Q. So f (x) > q and g(x) < q, so f (x) > q > g(x). So f (x) > g(x). Since Q is countable, S is the countable union of the measurable sets f −1 (q, ∞]∩ g −1 [−∞, q) for q ∈ Q. The measurable sets form a σ-algebra, so are closed under countable unions. So S is measurable. (c) For x ∈ X we have f (x) 6= g(x) ⇐⇒ f (x) > g(x) or f (x) < g(x). So {x ∈ X : f (x) 6= g(x)} = {x ∈ X : f (x) > g(x)} ∪ {x ∈ X : g(x) > f (x)}. By part (b), both of the sets in this union are measurable, so {x ∈ X : f (x) 6= g(x)} is measurable. 6. Let f, g : X → [−∞, ∞] be two measurable functions. (a) Show that if α ∈ R and q ∈ Q then f −1 (q, ∞] ∩ g −1(α − q, ∞] is a measurable set. (b) Suppose that g(x) 6= −∞ for all x ∈ X. The function f + g is then well defined. Let α ∈ R. Show that if f (x) + g(x) > α then there is a rational number q with α − g(x) < q < f (x). Deduce that [ f −1 (q, ∞] ∩ g −1(α − q, ∞]. (f + g)−1(α, ∞] = q∈Q Why does this show that this set is measurable? (c) Deduce that f + g is a measurable function. 4 Solution. (a) Since f and g are measurable, f −1 (q, ∞] and g −1 (α − q, ∞] are both measurable sets. The measurable sets form a σ-algebra, so are closed under [countable] intersections. So f −1 (q, ∞] ∩ g −1(α − q, ∞] is measurable. (b) If f (x) + g(x) > α then f (x) > α − g(x), so there is a rational number q in the non-empty open interval (α − g(x), f (x)); then α − g(x) < q < f (x). S Let S = q∈Q f −1 (q, ∞] ∩ g −1(α − q, ∞]. If x ∈ (f + g)−1(α, ∞] then f (x) + g(x) > α, so there is a rational number q ∈ Q with α − g(x) < q < f (x). So f (x) > q ⇐⇒ x ∈ f −1 (q, ∞] and g(x) > α − q ⇐⇒ x ∈ g −1 (α − q, ∞]. So x ∈ f −1 (q, ∞] ∩ g −1 (α − q, ∞]; so x ∈ S. Conversely, if x ∈ S then there is q ∈ Q with x ∈ f −1 (q, ∞] ∩ g −1 (α − q, ∞], so f (x) > q and g(x) > α − q, so f (x) + g(x) > q + α − q = α, so x ∈ (f + g)−1 (α, ∞]. So S = (f + g)−1(α, ∞], and this is the countable union of the measurable sets f −1 (q, ∞] ∩ g −1 (α − q, ∞] for q ∈ Q. So this set is measurable. (c) In (b) we showed that (f + g)−1 (α, ∞] is measurable for all α ∈ R. So f + g is measurable. 5